Implementation of Digital Information System to Enhance Quality of Patient’s Nutrition Service - Elyzabeth Sylviana Girsang; Cahya Tri Purnami; Farid Agushybana (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Hospital nutrition services aim to optimize patient’s nutritional status through the provision of appropriate diets. Currently, technological advancements can be utilized to support the management of nutrition services by developing digital information systems for meal provision. This study aims to describe the information systems that have been developed for hospital nutrition services and their benefits. The method used is a scoping review. Articles were collected from 3 databases: Scopus, PubMed, and Google Scholar. The keywords used in the search were: “Electronic Food Service” AND “Hospital” and “Nutrition Information System” AND “Hospital” AND “Service”. A total of 10 relevant articles were selected. The findings show that the developed information systems can be used by staff and patients. Systems for dietitians are designed to assist in assessing nutritional status and planning dietary interventions, while systems for patients enable them to choose and order their meals independently. The benefits include reducing staff workload, ensuring timely food distribution, decreasing errors in food delivery and food waste, and improving patient satisfaction. The conclusion, information systems provide valuable support in enhancing the quality of nutrition services and patient satisfaction.